Analysis of Competitive Advantages for PT. Bali Sundaram - Gera Dhea Guniyati; Agung Wahyu Handaru; Indra Pahala (MultiTech Publisher, 2024)
To remain a leading company in the highly competitive tourism industry in Bali, particularly among Tour & Travel businesses, it is essential for a business to determine the strategies it will implement. By setting the right strategies, the company can advance its business progress. This study aims to assess the internal conditions of PT. Bali Sundaram's travel business based on the Internal Factor Evaluation (IFE) matrix, evaluate the external conditions of the business using the External Factor Evaluation (EFE) matrix, and determine the strategies that should be applied by PT. Bali Sundaram. Data collection for this study was conducted through interviews, direct observations, and questionnaires. The data were analyzed using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results of the SWOT analysis show that the internal factor analysis (IFAS) score is 2.69 and the external factor analysis (EFAS) score is 3.34. The company is positioned in Quadrant II, which indicates